2016
DOI: 10.1080/15374416.2016.1204925
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Pathologic Adaptation Model of Community Violence Exposure in Male Adolescents of Color

Abstract: The current study examined a model of desensitization to community violence exposure—the pathologic adaptation model—in male adolescents of color. The current study included 285 African American (61%) and Latino (39%) male adolescents (W1 M age = 12.41) from the Chicago Youth Development Study to examine the longitudinal associations between community violence exposure, depressive symptoms, and violent behavior. Consistent with the pathologic adaptation model, results indicated a linear, positive association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 74 publications
(115 reference statements)
5
27
0
1
Order By: Relevance
“…Furthermore, results of the present study showed that, for both groups, proactive aggression had a stronger mediational effect on the link between witnessing violence and conduct problems than reactive aggression. This finding aligns with studies on chronic CVE and associated desensitization processes (i.e., emotional numbing and use of aggression increasingly being seen as acceptable) resulting in higher levels of externalizing behavior (Ng-Mak et al, 2004 ; Boxer et al, 2008 ; Mrug et al, 2016 ; Gaylord-Harden et al, 2017 ). Translating these findings to the present study, one might expect that those children and adolescents witnessing more violence in their neighborhoods may have also undergone desensitization processes that have led them to become more proactively aggressive.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, results of the present study showed that, for both groups, proactive aggression had a stronger mediational effect on the link between witnessing violence and conduct problems than reactive aggression. This finding aligns with studies on chronic CVE and associated desensitization processes (i.e., emotional numbing and use of aggression increasingly being seen as acceptable) resulting in higher levels of externalizing behavior (Ng-Mak et al, 2004 ; Boxer et al, 2008 ; Mrug et al, 2016 ; Gaylord-Harden et al, 2017 ). Translating these findings to the present study, one might expect that those children and adolescents witnessing more violence in their neighborhoods may have also undergone desensitization processes that have led them to become more proactively aggressive.…”
Section: Discussionsupporting
confidence: 84%
“…However, findings also underline that in the presence of a high rate of CVE as well as severe levels of conduct problems, eventually a ceiling effect sets in, where the strength of association between the two variables is reduced or even becomes negative. Gaylord-Harden et al ( 2017 ) specifically investigated the cumulative impact of CVE on psychopathology in a male adolescent community sample. CVE was found to show a curvilinear relationship with internalizing problems and a positive linear relationship with violent behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, boys engage in more confrontative coping strategies (Rasmussen et al, 2004), which may increase their risk for future violent victimization (Dong, Morrison, Branas, Richmond, & Weibe, 2019). This is particularly critical because previous research examining the consequences of chronic exposure to violence suggests that youth become desensitized over time, such that youth report less psychological distress (Ng-Mak, Salzinger, Feldman, & Stueve, 2004), depression (Gaylord-Harden, So, Bai, Henry, & Tolan, 2017), and anxious/depressive symptoms (Kennady & Ceballo, 2016), while aggressive behavior increases linearly and exposure to violence becomes more chronic. Subsequently, it is important to examine perceptions of safety, safety strategies, and how they implicate behavior and daily functioning.…”
Section: Safety Strategies and Resiliencementioning
confidence: 99%
“…Studies suggest that the psychological injury endured when people undergo traumatic experiences—such as dehumanization—can fuel them to perpetrate further violence (Gillikin et al., ). Furthermore, psychologists link high‐violence neighborhoods to chronic histories of trauma, commonly characterizing low‐income communities of color with numerous violence risk factors (Gaylord‐Harden, So, Bai, Henry, & Tolan, ; Sinha & Rosenberg ). However, complicating this literature, our data reveal that dehumanization was a collective experience in over‐policed neighborhoods with the potential to also produce a recognition of shared humanity, antiviolence organizing, and a collective approach to healing (Ginwright, ).…”
Section: Resultsmentioning
confidence: 99%